Green analytical method for quantification of Secnidazole in tablets by FourierTransform Infrared Spectroscopy (FTIR) - Gonçalves de Souza Lima, Jéssica; Aparecida de Marco, Bianca; Regina Nunes Salgado, Hérida (Drug Analytical Research, 2026)
Secnidazole is a medicine widely used in the treatment of bacterial and protozoal diseases. The free sale of this drug allows its easy access to the population and for this reason, the studies that involve the analysis of the quality control of this drug are extremely important to keep the results safe and reliable. Considering the great pharmacotherapeutic application of secnidazole and the great importance of developing new analytical methods that contribute to the environmen, the study was based on the development and validation of a new sustainable analytical method by Fourier-transform infrared spectroscopy (FT-IR) to identify and quantify secnidazole tablets. The method was duly validated according to the ICH guidelines, presenting precision, accuracy, selectivity, robustness and linearity in the concentration range of 0.5-1.3 mg/pellet. The application of this method in addition to being safe and reliable is highly favorable from an economic point of view since there is a significant reduction in the use of production costs as solvents and raw material, being fast and simple and can also be applied to other medicines.